No small matter : science on the nanoscale - Frankel, Felice; Whitesides, G. M. (Cambridge, Mass. : Belknap Press of Harvard University Press, 2009)
A small revolution is remaking the world. The only problem is, we can't see it. Images and descriptions reveal the virtually invisible realities and possibilities of nanoscience. An introduction to the science and technology of small things. An overview of recent scientific advances that have given us our ever-shrinking microtechnology - for instance, an information processor connected by wires only 1,000 atoms wide. New methods are described that are used to study nanostructures, suggest ways of understanding their often bizarre behavior, and outline their uses in technology. The various means of making nanostructures are explained and speculated about their importance for critical developments in information processing, computation, biomedicine, and other areas. No Small Matter considers both the benefits and the risks of nano/microtechnology - from the potential of quantum computers and single-molecule genomic sequencers to the concerns about self-replicating nanosystems.
Santa Maria -- Feeling is seeing -- Quantum cascades -- Water -- Single molecules -- Cracks -- Nanotubes -- Vibrating viola string -- Prism and diffraction -- Duality -- Interference -- Quantum apple -- Molecular dominoes -- The cell in silhouette -- Laminar flow -- The wet fantastic -- Fingers -- Soap bubbles -- The cell as circus -- Ribosome -- Bacterial flagella -- Life as a jigsaw puzzle -- As the wheel turns -- Quantum dots and the cell -- Sequencing DNA -- Molecular recognition -- Harvesting light -- The elegance of simple animals -- Antibodies -- Virus -- Writing with light -- Eleanor Rigby -- Abacus -- Counting on two fingers -- Babbage's computing engine -- Computers as waterworks -- Microreactor -- Templating -- Catalyst particles -- Christmas-tree mixer -- Self-assembly -- Synthetic nose -- Millipede -- e-paper and the book -- Lateral-flow assay as crystal ball -- Testing drugs in cells -- Cooling the fevered brain -- Phantoms -- Privacy and the nest -- Soot and health -- Robots -- Fog -- In sickness and in health -- The internet -- Reverse osmosis membrane -- Nuclear reactions -- Flame -- Fuel cell -- Solar cell -- Plants and photosynthesis.
Includes bibliographical references (p. 164).
Keywords: Nanoscience; Nanobilim; Nanotechnologie